ASUHAN KEBIDANAN PADA IBU NIFAS NY”E” P2A0H2 DI RUMAH BERSALIN BUNDA PUJATEMBILAHAN TAHUN 2019 - Yolanda Novitri; Madinah (Jurnal Kesehatan Husada Gemilang, 2021)
Approximately 60% of maternal deaths occur after childbirth and nearly 50% of it happened in the first 24 hours after childbirth. The total of post-partum mothers at the Bunda Puja Maternity Hospital Tembilahan were 271 people which from January to December 2019 was 195, and January to July 2020 was 76. The aim of this care is to provide midwifery care for Mrs. "E" P2A0H2 at Bunda Puja Maternity Hospital Tembilahan that was documented in SOAP form and analyzed their gaps in theory and practice. This care was carried out at the Bunda Puja Maternity Hospital Tembilahan on July 7th to August 4th, 2019. The data collection method used midwifery management by using varney mindset and documented in SOAP form. The results show there were gaps in theory and practice in the management of the third postpartum visit, where the mother did not do postpartum exercise due to the absence of the trainer / instructor, postpartum gymnastics facilities and infrastructure while on the third visit one of the care provided is postpartum exercise. It is hoped that it can maintain and improve midwifery care in the normal postpartum period, can facilitate postpartum gymnastics and for midwifery care centers can make overall visits to postpartum mothers.